2021
DOI: 10.1186/s13054-020-03431-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of metabolic acidosis with sodium bicarbonate in the ICU: An international observational study

Abstract: Background Metabolic acidosis is a major complication of critical illness. However, its current epidemiology and its treatment with sodium bicarbonate given to correct metabolic acidosis in the ICU are poorly understood. Method This was an international retrospective observational study in 18 ICUs in Australia, Japan, and Taiwan. Adult patients were consecutively screened, and those with early metabolic acidosis (pH < 7.3 and a Base Excess < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
3
17
0
2
Order By: Relevance
“…The above findings in this study can be summarized as follows: ( Vincent and Abraham, 2006 ): There was no association between SB infusion treatment and reduced ICU or hospital mortality overall in elderly septic patients with acute MA or in the subgroup of acute SMA; ( Yahav et al, 2016 ); SB infusion was associated with reduced both ICU and hospital mortality for elderly septic patients in the subgroup of acute MMA. The current studies demonstrated that acute MA was frequently observed in the older critical patients with sepsis, and SB was commonly used in such patients but there was lack of evidence about its effect on mortality ( Englert and Ross, 2015 ; Ganesh et al, 2016 ; Martin-Loeches et al, 2019 ; Fujii et al, 2021 ). Therefore, this is the first clinical investigation providing the evidence that SB infusion could improve both ICU and hospital survival for elderly septic patients with acute MMA.…”
Section: Discussionmentioning
confidence: 87%
“…The above findings in this study can be summarized as follows: ( Vincent and Abraham, 2006 ): There was no association between SB infusion treatment and reduced ICU or hospital mortality overall in elderly septic patients with acute MA or in the subgroup of acute SMA; ( Yahav et al, 2016 ); SB infusion was associated with reduced both ICU and hospital mortality for elderly septic patients in the subgroup of acute MMA. The current studies demonstrated that acute MA was frequently observed in the older critical patients with sepsis, and SB was commonly used in such patients but there was lack of evidence about its effect on mortality ( Englert and Ross, 2015 ; Ganesh et al, 2016 ; Martin-Loeches et al, 2019 ; Fujii et al, 2021 ). Therefore, this is the first clinical investigation providing the evidence that SB infusion could improve both ICU and hospital survival for elderly septic patients with acute MMA.…”
Section: Discussionmentioning
confidence: 87%
“…Treatment with sodium bicarbonate should be reserved for patients in ICU with high anion-gap metabolic acidosis, particularly severe lactic acidosis. It is independently associated with increased mean arterial pressure and reduced ICU mortality in this group of patients [17,18]. But sodium bicarbonate alone may not be sufficient to correct the severe acidosis seen in these patients.…”
Section: Discussionmentioning
confidence: 94%
“…A recently published international observational study conducted in 18 ICUs in Australia, Japan, and Taiwan reported that 14% (1292/9437) of critically ill patients had moderate or severe metabolic acidosis [9]. The median incidence of metabolic acidosis at a study ICU was 172.5 patients/year, suggesting that the management of metabolic acidosis is a relevant issue in patient care in the ICU.…”
Section: Epidemiology Of Metabolic Acidosis In the Icumentioning
confidence: 99%
“…A recent international observational study revealed that 18% of patients with moderate or severe metabolic acidosis receive sodium bicarbonate in current clinical practice [9]. However, the total amount of sodium bicarbonate given during the first 24 h of metabolic acidosis was 110 mmol, which was not adjusted for body weight or base excess.…”
Section: How We Manage Metabolic Acidosis In the Icumentioning
confidence: 99%